PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA - Ian Nurpatria Suryawan; Richard Andrew (Media Riset Bisnis & Manajemen, 2013)
Research is intended to test influence Motivation against Job Satisfaction work lecturer at Economics Faculty, "T" University in Jakarta. The sample used purposive sampling technique, where samples selected totaled 100 respondents who works as a lecturer at the Economics Faculty, "T" University during at least 24 months. Instrument analysis of data used is multiple regression analysis by the aid SPSS program. Based on the results of the study found that there is a positive relationship but tends to be weak between satisfaction job satisfaction variables namely only capable of amounting to 22.1% described by the motivational variable while another 77,9% is explained by the variation of variables outside motivation.Keywords : Motivation, Job satisfaction, University